Prevalence Of Dental Caries With Pulpitis Among Diabetic Patients : A Retrospective Study - SANGAR, SIVESH; VADIVEL, JAYANTH KUMAR; RAMANATHAN, VISALAKSHI (The journal of contemporary issues in business and government, 2021)
Aim: The aim of the present study was to assess the prevalence of diabetes in patients with dental caries associated with pulpitis in diabetic patients attending Saveetha Dental Hospital, Chennai. Materials and Method: This study was done by analysing the archived case records of Saveetha Dental College. From the existing records a total of 2268 patients with pulpitis were recorded in the time interval between June 2019 and March 2020. Each of the case records were analysed and patients with diabetes mellitus were segregated noted down. The presence of diabetes mellitus as recorded was based on the self reporting by patients. The study was approved by the Institutional Ethics Committee. Results:A total of 2268 patients with pulpitis were identified and 248 patients had self declared diabetes. The overall prevalence of diabetes in the patients was 10.93%. There was a slight male occurrence of the disease and an increase in incidence of diabetes was noted with advancing age in the given sample.The highest number of diabetics were seen in the 41-60 age group. Data analysis was done using a chi-square test between the presence of diabetes and gender (chi-square-0.256;df- 1;p-0.032) we found the results were statistically significant(P<0.05). Data analysis was done using a chi-square analysis between the presence of diabetic conditions and age groups (chi square - 31.888,df - 4,p-0.02) we found the results were statistically significant (P<0.05). Conclusion: From the study it is noticed that there is an increase in the incidence of diabetes in patients with pulpitis signifying that the diabetic patients are prone to infections. However all the diabetic patients in this study were self reported diabetic patients.